Psychoanalysis, Marxism and Semiology: Identity, Value and the Sign - van Wyk, Johan (PINS-Psychology in Society, 2026)
This article explores the overlap between value, sign and identity - concepts central to Marxism, semiology and psychoanalysis. This overlap is possibly best represented in coins, stamped with the emblems of prominent merchants, kings or nations, and functioning as signs guaranteeing value, as well as embodying a certain identity.